SIMULATION OF XRD PATTERNS AS A OPTIMAL TECHNIQUE FOR STUDYING GLACIAL AND INTERGLACIAL CLAY MINERAL ASSOCIATIONS IN BOTTOM SEDIMENTS OF LAKE BAIKAL - Solotchina E.P.; Prokopenko A.A.; Vasilevsky A.N.; Gavshin V.M.; Kuzmin M.I.; Williams D.F. (My University, 2002)
A new method is proposed for modelling complex X-ray diffraction patterns effectively. The method is based on the calculation of the interference function of the onedimensional disordered crystals with finite thickness. First, we calculated the diffraction effects from structures of individual mineral phases with different layer defects modelled according to the Reynolds’ algorithm. To fit the theoretical to the observed XRD patterns more accurately, we then used a specially developed optimization procedure. This iterative procedure selects the optimal set of chemical and structural parameters (probability and domain size) and yields consistent solutions. The composition of the clay component in bottom sediments of Lake Baikal relates strongly to glacial/interglacial climate cyclicity. Besides changes in the relative abundance of illite and illite/ smectites between glacial and interglacial periods, significant differences are observed in the crystal chemistries and structures of layered minerals. A change from chlorite during glacial periods to chlorite-smectite during interglacials is probably indicative of the weathering processes in the watershed. Changes in the degree of ordering, in domain size and grain-size distribution of illitesmectites imply differences in genesis of this mineral phase in different palaeoenvironments. These findings further strengthen the case for using clay minerals in the sedimentary record of Lake Baikal as palaeoclimate indicators. One of our findings was that none of the fractions separated by Stokes’ settling is representative of the bulk sample for either the glacial or interglacial intervals. For the interglacial sample, illitesmectite was concentrated in the <2 μm fraction whereas, for the glacial sample, most of illitesmectite is contained in the <1 μm fraction. The selective use of one fraction is yet another potential source of uncontrolled errors that has to be avoided. We suggest using X-ray patterns of bulk samples as a preferred method of analysis of Lake Baikal (and other) sediments.